Public Policy, Celebrity, Popular Culture and the Making of a Spiritual Industrial Marketplace in Post War America: A Review of The Spiritual-Industrial Complex and Oprah: The Gospel of an Icon - Martin, Lerone (American Studies, 2013)
This review essay reviews: The Spiritual-Industrial Complex: America’s Religious Battle Against Communisim in the Early Cold War, by Jonathan P. Herzog; Oprah: The Gospel of an Icon, by Kathryn Lofton.